David Busch's DJI Mini 3/Mini 3 Pro Guide to Drone Photography - Busch, David D. (Rocky Nook, 2024)
The complete guide to mastering your drone! David Busch's DJI Mini 3/Mini 3 Pro Guide to Drone Photography is your comprehensive resource and reference guide to capturing high quality photographic still images and high-definition video with the ultra-compact DJI Mini 3 and Mini 3 Pro aircraft. These highly affordable, easy-to-fly Unmanned Aircraft Systems (UAS) are taking off all over the United States and worldwide. Photo and video enthusiasts as young as 16 can capture compelling images and video for personal use, social media, and YouTube channels. The first model-specific guide for the Mini 3 and Mini 3 Pro from David Busch, the world's #1 selling camera guide author, this book will lead you through registration, pre-flight prep, and mastery of every feature in a concise, fun, and straightforward way. Filled with detailed how-to steps and full-color illustrations, David Busch's DJI Mini 3/Mini 3 Pro Guide to Drone Photography covers the drones' capabilities in depth, from understanding the FAA rules and regulations, to taking your first photos and videos. You'll learn how to perform basic aerial moves and use the two Mini aircrafts' built-in flight tools. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your drone's capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence with the DJI Mini 3 and Mini 3 Pro today.